Formateur en ligne : vers un modèle d'action - Jacques Béziat (Centre National d'Enseignement à Distance, 2012)
From an e-learning practice within a strongly instrumented learning environment, we develop an action model of trainer on line. Our observation data comes from exchanges with students and tutors. The approach is systemic ant it explores the necessary evolution of the trainer tasks, in e-learning, to keep educational link.